OPTIMALISASI TAMAN BACAAN MASYARAKAT RUMAH KREATIF WADAS KELIR DALAM PENGUATAN LITERASI INFORMASI DI ERA DIGITAL - Nugroho, Rafli Adi; Wulandari, Suci; Farihati, Lulu (Perpustakaan Nasional RI, 2024)
In today's digital era, so much information can be easily found. This amount of information, which is often uncontrollable, is a challenge in itself in various aspects of life. Information literacy is then present as one of the strategies in dealing with this challenge. Information literacy is the ability to access, understand, and utilize information effectively, which is becoming increasingly important in the digital era. The Community Reading Park (TBM) serves as a forum for strengthening information literacy, especially among people who have limited access to digital information sources. This study uses a field qualitative method with the aim of analyzing the role of TBM in strengthening information literacy in the digital era. The approach used includes observation, interviews, and documentation to explore data on the role of TBM in helping people make better use of information in the digital era. This research was conducted at TBM Rumah Kreatif Wadas Kelir. The results of the study show that TBM Rumah Kreatif Wadas Kelir has made significant efforts in strengthening information literacy in its community through digital training programs, the provision of relevant information sources, and cooperation with local communities. Despite several obstacles, such as limited facilities and digital capabilities of participants, TBM Rumah Kreatif Wadas Kelir still managed to have a positive impact that was felt directly by community members.